Instagram Usage in Learning English: A Literature Review - Rizal Nur Rasyiid; Maulina Maulina; Celso P. Resueňo; Rahmat Nasrullah; Tri Indah Rusli (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
The social media of Instagram, one of the most used mediums to connect online, is used to build relations and correlations among individuals to support long-distance interaction. Educators and researchers often apply it in global contexts for educational purposes like teaching and researching English vocabulary learning. Moreover, vocabulary is essential in order to enhance EFL learner’s skills. This study presents an analysis of Instagram usage in learning English Vocabulary. The purpose is to analyze how Instagram can assist EFL students in learning vocabulary and investigate whether or not Instagram improves vocabulary comprehension. The authors also review journals taken from several trustworthy sources like Research Gate, Turkish Online Journal of Educational Technology, Arab International English Journal, Springer link, Atlantis press, and Science Direct.